Influence of aging in the temperature range 250–350 °C on the tribological performance of a WC-CoCr coating produced by HVOF. (September 2018) - Rovatti, L.; Lecis, N.; Dellasega, D.; Russo, V.; Gariboldi, E.
Abstract: Coatings made of tungsten carbides in a metallic matrix are key materials for wear-resistant industrial components. However, the thermal stability could represent a critical parameter for the future development of these WC-based composites, in view of increasing their service temperature. In the present study the evolution after thermal exposure of a WC-CoCr coating deposited by HVOF in the temperature range 250–350 °C up to 345 h was monitored. The analysis was carried out combining surface characterization (SEM, GDOES and Raman) with hardness and tribological behaviour. The results showed a detrimental effect of the oxidation on the wear behaviour of the WC-based material, already noticeable after short aging at the upper temperature. In fact, while in the untreated samples the worn products contributed to achieve a low and stable friction coefficient (COF), in the aged coatings a COF increase was observed. The worsening was due to the presence of porous and not-protective oxides grown during aging that overcome the lubricant oxidative effect occurred during sliding. Graphical abstract: Unlabelled Image Highlights: The effect of heat treatments in air on HVOF WCCoCr coatings is studied up to 350 °C. Surface evolution is characterized by hardness, pin on disk, GDOES, Raman and SEM. The friction coefficient is below 0.25 in the as received coating. Long aging produces not-protective oxides that increase wear rate and COF above 0.4.